2011
DOI: 10.1038/ni.2068
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor Tsc1 enforces quiescence of naive T cells to promote immune homeostasis and function

Abstract: The mechanisms that regulate T cell quiescence are poorly understood. We report that tuberous sclerosis complex 1 (Tsc1) establishes a quiescence program in naive T cells by controlling cell size, cell cycle entry, and responses to T cell receptor stimulation. Loss of quiescence predisposed Tsc1-deficient T cells to apoptosis that resulted in loss of conventional T cells and invariant natural killer T cells. Loss of Tsc1 function dampened in vivo immune responses to bacterial infection. Tsc1-deficient T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
350
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(365 citation statements)
references
References 49 publications
11
350
3
1
Order By: Relevance
“…Activation of mTORC1 and mTORC2 upon TCR stimulation depends on PI3K-AKT, as well as Ras guanyl releasing protein 1 (RasGRP1)-Ras-Erk1/2 pathways (10). Additional studies, including ours, have demonstrated that mTOR and its tight regulation by the tumor suppressor TSC1 play crucial roles in T-cell differentiation, survival, quiescence, and migration, as well as other immune cell development and function (11)(12)(13)(14)(15)(16)(17). However, the role of mTOR in iNKT cells is unclear.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Activation of mTORC1 and mTORC2 upon TCR stimulation depends on PI3K-AKT, as well as Ras guanyl releasing protein 1 (RasGRP1)-Ras-Erk1/2 pathways (10). Additional studies, including ours, have demonstrated that mTOR and its tight regulation by the tumor suppressor TSC1 play crucial roles in T-cell differentiation, survival, quiescence, and migration, as well as other immune cell development and function (11)(12)(13)(14)(15)(16)(17). However, the role of mTOR in iNKT cells is unclear.…”
mentioning
confidence: 89%
“…PLZF may function as a negative feedback mechanism to dampen mTORC1 activation. Hyperactivation of mTORC1 poses detrimental effects in other immune cells (12)(13)(14)(15)(16)(17). Fine-tuning of mTORC1 and PLZF activities may be crucial for the proper development and function of iNKT cells and many other cell types.…”
Section: Significancementioning
confidence: 99%
“…Tuberous sclerosis 1 (Tsc1), a negative regulator of mTORC1 signaling (26), has been implicated in T-cell homeostasis and anergy (27)(28)(29)(30). We and others have demonstrated that deletion of Tsc1 in naïve T cells disrupts their quiescence and survival and dampens T-cell-mediated primary responses to bacterial infection (27)(28)(29).…”
Section: Significancementioning
confidence: 99%
“…We and others have demonstrated that deletion of Tsc1 in naïve T cells disrupts their quiescence and survival and dampens T-cell-mediated primary responses to bacterial infection (27)(28)(29). To circumvent the crucial requirement of Tsc1 in naïve T-cell homeostasis, we developed a mouse model to specifically delete Tsc1 in antigen-experienced CD8 + T cells.…”
Section: Significancementioning
confidence: 99%
“…TSC1 and TSC2 proteins form a heterodimeric complex that acts as a functional unit and are closely involved in a wide range of cellular functions [10][11][12][13] . TSC1 enhances TSC2 activity by stabilizing TSC2 (ref.…”
mentioning
confidence: 99%